2014
DOI: 10.1002/2014gl062210
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying barotropic and baroclinic eddy feedbacks in the persistence of the Southern Annular Mode

Abstract: Understanding the persistence of the Southern Annular Mode (SAM) is important for the intraseasonal and decadal predictability of SAM. Using the ERA-40 and ERA-Interim reanalysis data, this study introduces a new method to quantify the relative roles of barotropic and baroclinic eddy feedbacks in the SAM persistence. Through a hybrid Eulerian-Lagrangian Finite Amplitude Wave Activity diagnostic, it is found that (i) transient wave activity is important in driving the SAM, but it provides a negative feedback to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 34 publications
1
51
1
Order By: Relevance
“…As the persistence of the SAM is mostly extended through the positive eddy‐zonal flow feedback in which both barotropic and baroclinic mechanisms play important roles [ Nie et al , ], in this study, we adopt the FAWA analysis [ Nakamura and Zhu , ] to investigate how the SAM‐induced SST anomaly can influence the barotropic and baroclinic processes in such positive feedback thus finally affect the SAM variability. Same as in Nie et al [, equation (1)], the FAWA (denoted by A ) is defined by the waviness of quasi‐geostrophic potential vorticity (PV, denoted by Q ) contours at a constant pressure level. Following the formalism, the eddy momentum flux convergence, which is the dominant forcing governing the variability of eddy‐driven jet, is rewritten as in Chen et al []: M1acos2ϕ()[uv]cos2ϕ∂ϕ=false∂p()f[vθ]θs/∂pbaroclinicfalsekeffa∂Qϕebarotropic∂A∂t+ΔΣ, where [] denotes the zonal average and ∗ denotes the eddy component.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…As the persistence of the SAM is mostly extended through the positive eddy‐zonal flow feedback in which both barotropic and baroclinic mechanisms play important roles [ Nie et al , ], in this study, we adopt the FAWA analysis [ Nakamura and Zhu , ] to investigate how the SAM‐induced SST anomaly can influence the barotropic and baroclinic processes in such positive feedback thus finally affect the SAM variability. Same as in Nie et al [, equation (1)], the FAWA (denoted by A ) is defined by the waviness of quasi‐geostrophic potential vorticity (PV, denoted by Q ) contours at a constant pressure level. Following the formalism, the eddy momentum flux convergence, which is the dominant forcing governing the variability of eddy‐driven jet, is rewritten as in Chen et al []: M1acos2ϕ()[uv]cos2ϕ∂ϕ=false∂p()f[vθ]θs/∂pbaroclinicfalsekeffa∂Qϕebarotropic∂A∂t+ΔΣ, where [] denotes the zonal average and ∗ denotes the eddy component.…”
Section: Methodssupporting
confidence: 91%
“…The persistence of the SAM is thought to be maintained by the positive feedback between the zonal mean zonal wind and the eddy momentum forcing [ Lorenz and Hartmann , ]. As shown by Nie et al [], both barotropic mechanisms [ Hartmann and Lo , ; Chen et al , ] and baroclinic mechanisms [ Robinson , ; Lorenz and Hartmann , ; Chen and Plumb , ; Zhang et al , ] contribute to this positive feedback.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in section 1, isolating and quantifying the eddy-feedbacks is another difficulty in developing a full mechanistic understanding of problems in which eddymean flow interaction plays an important role; examples of such problems include the dynamics of the Annular Modes and their overestimated persistence in GCMs (Feldstein and Lee 1998;Robinson 2000;Lorenz and Hartmann 2001;Simpson et al 2013a;Nie et al 2014), poleward shift of the midlatitude jets under climate change (Chen and Held 2007;Kidston et al 2011;Lorenz 2014) and troposphere-stratosphere coupling (Kushner and Polvani 2004;Song and Robinson 2004;Domeisen et al 2013). The EFMÊ E E and similar matrices for eddy-phase speed and eddy length-scale can be used to isolate and quantify the response of eddies to a given change in the mean-flow, which combined with well-controlled GCM experiments made possible usingM M M, can help with developing a deeper dynamical understanding of these problems.…”
Section: Applications Of the Lrf And Efmmentioning
confidence: 99%
“…Such methods include FDT, to construct LRFs, and lag-regression (Lorenz and Hartmann 2001;Simpson et al 2013b) and finite-amplitude wave-activity (Nakamura and Zhu 2010;Nie et al 2014), to diagnose eddy feedbacks. As an example, in Part 2 of this study, we useM M M to investigate why the LRF constructed using the FDT performs poorly in some cases.…”
Section: Applications Of the Lrf And Efmmentioning
confidence: 99%
“…In recent years, observational studies with high-resolution satellite data (Nakamura et al 2004;Small et al 2008) and numerical studies with high-resolution GCM Taguchi et al 2009;Sampe et al 2010;Czaja and Blunt 2011;Feliks et al 2004Feliks et al , 2007Feliks et al , 2011 have shown that the SST anomalies associated with midlatitude oceanic front zones can influence the time-mean atmospheric circulation beyond planetary boundary layer. Therefore, the transient eddies not only play an important role in driving and maintaining midlatitude atmospheric circulation (Ren et al 2011;Xiang and Yang 2012;Zhang et al 2012;Nie et al 2013Nie et al , 2014, but also may act as a main dynamical process through which the midlatitude ocean thermal condition can affect the atmosphere (Ren et al 2007). …”
Section: Introductionmentioning
confidence: 99%